ARSITEKTUR RUMAH PANGGUNG MASYARAKAT MELAYU DI JAMBI KOTA SEBERANG PERIODE KESULTANAN HINGGA KEMERDEKAAN - Rahmaina, Irda; Heidi Karmela, Siti; Yanto, Ferry (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2024)
This research is a cultural history, an effort to look for cultural morphology, study structure, find the central concept of a culture, with the object of research being the Jambi area of Seberang City which is the center of Jambi Malay Culture, including the stilt house. The aim of the research is an answer to the proposed problem formulation, namely: describing the combination of cultural acculturation in the architecture of stilt houses in Jambi across the city and how to maintain the architecture of stilt houses. The research method used is the historical method including heuristic, criticism, interpretation and historiography stages. The sources used are literature studies, documents, archives and interviews. Home is a place to live, live, eat, sleep, do activities and chat with family.